Traditional management affects the phenotypic diversity of fruits with economic and cultural importance in the Brazilian Savanna - Sousa Júnior, José Ribamar; Collevatti, Rosane Garcia; Lins Neto, Ernani Machado Freitas; Peroni, Nivaldo; Albuquerque, Ulysses Paulino (Agroforestry systems, 2018)
The management of plant populations may cause phenotypic changes in the characteristics of a plant that is targeted by human selection over time, which can therefore lead to the domestication process. Studies about this approach have shown that managed plant populations have the most interesting features for use by human populations because they have more productive plants and larger fruits. To evaluate this effect, the traditional management of Caryocar coriaceum Wittm (pequi) in the Chapada do Araripe region of Northeast Brazil was studied by using a morphometric and ethnobotanical approach. A morphometric analysis of the fruits was conducted, during which the plants were recorded to the following three different management regimes: cultivation, in situ management (collection) and incipient management (the tolerance and protection of individuals). To test the hypothesis that people perceive natural morphological variations in the fruits, local people perception was assessed through different methods. To assess the possible influence of management regimes on fruit morphology, 40 reproductive individuals cultivated, 40 managed in situ and 36 individuals under incipient management were randomly selected, and 20 fruits of each were collected for the morphometric analyses. The fruits from individuals grown under the cultivation system were significantly different from the individuals who were managed in situ and from those under incipient management. The perception study showed that local people perceive great morphological diversity among the study populations, which was consistent with the findings of the morphometric analyses. Based on these results, it could be said that C. coriaceum is in the early stage of the domestication process.